2009
DOI: 10.1007/s00253-008-1841-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and characterization of Trichoderma reesei cellulase and xylanase promoters

Abstract: Comprehensive analyses on promoters of four cellulase and one xylanase genes of Trichoderma reesei were performed expressing a single reporter uidA from Escherichia coli to construct highly functional cellulase-overproducing strains. GUS amount expressed under each promoter correlated entirely with each mRNA amount, suggesting that GUS production was controlled at the transcriptional level. The uidA transcript levels were much lower than the native gene mRNAs, but they were produced in proportion to the mRNA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…2, 4) and heterologous gus. 18) We have found that no xyn3 transcripts were detected in T. reesei QM 9414, although the same xyn3 structural gene and 5 0 -upstream region were present. 7,39) We also observed that expression of xyn3 in QM6a was very weak compared to that of the PC-3-7 (unpublished data).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…2, 4) and heterologous gus. 18) We have found that no xyn3 transcripts were detected in T. reesei QM 9414, although the same xyn3 structural gene and 5 0 -upstream region were present. 7,39) We also observed that expression of xyn3 in QM6a was very weak compared to that of the PC-3-7 (unpublished data).…”
Section: Discussionmentioning
confidence: 93%
“…The GUS amounts expressed under the cbh1, cbh2, egl1, egl3, and xyn3 promoters were, relative to cbh1, 100, 20, 25, 5, and 10%. 18) Because disruption of cbh1, cbh2, and egl1 lowers cellulase activity, we propose that minor promoter egl3 and xyn3 are suitable for homologous recombination, since deletion of egl3 and xyn3 does not affect the cellulase activity. Thus, the egl3 and xyn3 promoters are optimal for the expression y To whom correspondence should be addressed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, T. reesei produces cellulase component (endoglucanase and exoglucanase) in high amount with excellent properties such as thermostability and catalytic efficiency but it lacks sufficient amount of β-glucosidase. Researchers therefore have heterologously expressed exogenous β-glucosidase genes in T. reesei under strong promoter in order to enhance its β-glucosidase activity so that cellulose hydrolysis rate was improved considerably [112,187,190,191,192]. Majority of recombinant fungal β-glucosidase belong to glycoside hydrolase family 3.…”
Section: Cloning and Expression Of Microbial β-Glucosidasesmentioning
confidence: 99%
“…However, these promoters are either constitutively active and growth related (e.g., the Aspergillus niger glyceraldehyde-3-phosphate dehydrogenase promoter, PgpdA) or dependent on the carbon or nitrogen source (e.g., A. niger PglaA and PinuE, Aspergillus nidulans PalcA, Neurospora crassa Pqa-2, Ustilago maydis Pcrg1 and Pnar1, and Trichoderma reesei Pcbh1), and some are also leaky (e.g., PinuE and Pqa-2) (7,22,36,37). In search of promoters that are tight, tunable, and metabolism independent, three systems have recently been tested for application in filamentous fungi: the thiamine promoter system (PthiA) in Aspergillus oryzae (40), the human estrogen receptor (hER␣) system in A. nidulans and A. niger (32), and a system based on the Escherichia coli tetracycline resistance operon (Tet) in Aspergillus fumigatus (45).…”
mentioning
confidence: 99%